Predictors of possible exposure to rabies in travellers: A case-control study. Issue 47 (May 2022) - Bantjes, S.E.; Ruijs, W.L.M.; van den Hoogen, G.A.L.; Croughs, M.; Pijtak-Radersma, A.H.; Sonder, G.J.B.; Swaan, C.M.; Haverkate, M.R.
Abstract: Background: Timely administration of post-exposure prophylaxis (PEP) can prevent rabies. For non-vaccinated persons, PEP consists of multiple vaccinations and rabies immunoglobulin (RIG) on indication. Since RIG is scarce, the need for PEP could be restricted through preventing animal contact and pre-exposure vaccination. We aimed to identify determinants for possible rabies exposure among travellers to provide more targeted pre-travel advice. Method: A case-control study was performed. Cases were defined as persons with a possible rabies exposure (category II or III injury according to WHO classification guidelines) in a rabies endemic country. Controls did not report exposure during travel. Multivariable logistic regression was performed. Results: 229 cases and 1427 controls were included. Predictors (p < 0.05) of possible rabies exposure were young age, male sex, travelling to Western or Southeastern Asia, visiting a monkey park, pet ownership, previously visited the same country and considering oneself an experienced traveller. Negative predictors were travelling for business, visiting friends and relatives, and fear of animals. Conclusions: Pre-travel advice should take the identified predictors into account to provide better targeted information and pre-exposure prophylaxis.